AN AN ENUMERATIVE STUDY ON GARBHA-AVKRANTI FROM SUSRUTA-SHARIRA WSR TO LANGMAN’S MEDICAL EMBRYOLOGY - Sharma Giriraj G; *Sharma Pooja (International Journal of Ayurveda and Pharma Research, 2019)
The Garbhaavkarnti is the stage that describes the process of the growth of cell from intra-uterine life to post natal stage. The Garbhaavkranti mainly deals with the pre-natal life i.e. the foetal period and other related processes. This period is minutely envisioned by Langman’s medical embryology, and in Susurta Sharira we have got more detailed version of pre-natal period. The Garbha-avkranti word signifies the Garbh i.e. zygote and Avkranti or Avatarana i.e. different stages of development of zygote. Garbhaavkranti is a process in which different stages of formation of Garbha is mentioned. Garbha (zygote) is formed from the uniparental inherent cells known as sperm and ovum. There are some special characteristics that combine or fuse together along with 24 other Gunas like Avyakta, Mahana, Ahankara, Prakriti Tatva and Bhava i.e. gene and chromosomes. There is no single way that may lead to the formation of Garbha. Matraja Bhava (maternal inheritance factor) is present in Aartava which further shows the quality of Aagnaya feature i.e. the mitochondria of ovum. The importance of embryology at that time was known by Susruta & the criteria for good progeny & the process by which embryo develops was all known to them in subtle level. It is fascinating to conclude that they knew about all this without the technological advances which are available today. The importance of healthy mother & father in phase of conception is shown in this Garbhavkranti. This gives the idea of unhealthy reasons and gives broad scale treatment for infertility cases. The Garbhaavkranti (embryology) is always a matter of mondo concern to medical field. So, in this article the Susurta Sharira Grabhavkranti is discussed precisely thereby referring to Langman’s medical embryology for testimonial based study.